Technology-Based Startup Ideas and MVP Development: A Digital Literacy Perspective among High School Students - Ince Ahmad Zarqan; Dimas Yudistira Nugraha; Ganda Sitompul; Fernando Sihotang; Scherly Hansopaheluwakan; Adli Abdillah Nababan (Journal of Management and Business Analytics, 2026)
The rapid growth of digital technologies has created new opportunities for entrepreneurship among younger generations, including high school students. This study explores the emerging trends of technology-based startup ideas and evaluates the potential for Minimum Viable Product (MVP) development from the perspective of digital literacy. Using a descriptive–qualitative approach, data were collected from student business proposals, pitch decks, and prototype outputs generated during a startup competition for high school students. The analysis categorized startup ideas into various technological domains such as fintech, edtech, agritech, and health tech, while also assessing the quality and feasibility of MVPs based on lean startup principles. Findings reveal that students demonstrate strong creativity in problem identification and solution design, yet often face challenges in translating ideas into functional MVPs due to limited technical capacity. Moreover, higher levels of digital literacy—particularly in digital creativity, technological adaptability, and collaborative skills—were positively correlated with the quality of MVP outcomes. This study highlights the importance of integrating digital literacy into early entrepreneurship education, suggesting that fostering these competencies can enhance the capacity of young innovators to develop feasible and impactful technology-driven startups.